Google Classroom in EFL Writing: Students’ Perceived Improvement and Interview-Based Insights into Feedback–Revision Cycles - Sudiani, Sudiani; Zuhdi, Herman (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2025)
This study examines students’ perceived improvement in EFL writing when using Google Classroom (GC), with particular attention to mechanisms related to asynchronous feedback and revision cycles enabled through GC–Google Docs. A mixed-methods design was employed, involving a questionnaire administered to 100 EFL students and semi-structured interviews with 10 students at Sekolah Tinggi Ilmu Syariah Haji Abdul Rasyid. Descriptive survey results show that 75% of respondents perceived GC as helpful for improving writing, while 25% did not. Patterns across usage categories suggest a positive gradient between frequency of GC use and perceived improvement: students who used GC daily reported higher perceived improvement than those who used it less frequently. Interview findings indicate that perceived improvement is primarily associated with repeated engagement in feedback–revision cycles, where students check lecturer comments, interpret feedback, and revise drafts iteratively. Students also emphasized that the usefulness of GC depends on the specificity and actionability of lecturer feedback, the analytical quality of peer feedback, and contextual constraints such as internet stability and device access. Because outcomes are self-reported, findings are interpreted as evidence of perceived effectiveness and process-level mechanisms rather than objectively verified performance gains. The study recommends designing GC-based writing instruction around structured multi-draft tasks, actionable feedback practices, and scaffolded peer review, alongside institutional support for infrastructure and lecturer capacity building.